2019
DOI: 10.1177/0731121419859297
|View full text |Cite
|
Sign up to set email alerts
|

“Not an Environmentalist”: Strategic Centrism, Cultural Stereotypes, and Disidentification

Abstract: Birding has long been associated with environmental activism, from its origins as a scientific hobby in the nineteenth century to today’s citizen scientist birders. My research with birders shows that despite their political activism, personal actions, and ecological beliefs, many disidentify as activists or environmentalists. Using data from 30 in-depth interviews and three years of ethnographic research with birders, I argue their disidentification comes from two interrelated sources. First, these birders fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…However, each respondent interpreted their environmental behavior as part of a particular identity. This is consistent with research that has found that individuals can disidentify with environmentalist terminology based on particular conceptions of terms while still holding behavior standards that would be defined as "environmentalist" by others (Cherry 2019). This article explores the pathways to developing the identity standards that include environmental movement participation from the perspective of respondents.…”
Section: Datasupporting
confidence: 71%
“…However, each respondent interpreted their environmental behavior as part of a particular identity. This is consistent with research that has found that individuals can disidentify with environmentalist terminology based on particular conceptions of terms while still holding behavior standards that would be defined as "environmentalist" by others (Cherry 2019). This article explores the pathways to developing the identity standards that include environmental movement participation from the perspective of respondents.…”
Section: Datasupporting
confidence: 71%
“…Regarding the personalities of CSs, it would be interesting to further investigate to what degree nature conservation is part of their identity. Given the established community of birders with their distinct identity, which differs from that of environmentalists [ 51 ], we might also find an identity of insecters ? Udall et al published in 2020 a theoretical framework of how to test identities in relation to other psychological variables relevant for pro-environmental behaviour [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…With these pathways far outweighing the barriers, many nature-related organizations could potentially be safe spaces to discuss climate change. Although these organizations tend to avoid con ict by choosing a centrist path 9 and their members tended to avoid talking about climate change, my ndings suggest that members were fairly uni ed in their concern about climate change. Some were even open-minded about talking about climate change.…”
Section: Discussionmentioning
confidence: 76%
“…There is copious literature on the environmental movement but little on movement-adjacent groups and their members. One such study of the Audubon Society found that birders tended to distance themselves from the environmental movement 9 .…”
Section: Introductionmentioning
confidence: 99%